STUDI PERAMALAN JUMLAH MAHASISWA SARJANA MENUJU VISI INDONESIA EMAS: PENERAPAN METODE SINGLE MOVING AVERAGE - Desviona, Nayla; Utama, Rifki Chandra; Masruroh, Marwah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The main focus of this research is to analyze the results of forecasting the number of undergraduate students in Indonesia using the single moving average method to support the vision of a Golden Indonesia. This research method uses quantitative methods through the application of descriptive methods, relying on secondary data taken through the official website of the Central Statistics Agency (BPS) and the Higher Education Database (PDDikti) for the 2020-2024 period. Forecasting data will be divided into two periods, then the results of forecasting are seen with the level of accuracy that will be measured using the MAPE, MSE, and MAD methods. The prediction results show that the number of students in 2025 will reach around 9.8 million, with the best level of accuracy in the two-year period, with a MAPE result of 3.59%. This method is effective for strategic planning, including facility provision, faculty allocation, and education policy development. The findings provide a foundation for policy makers in supporting a quality education system and realizing the golden generation in 2045.